Наукові дослідження — запорука сталого розвитку судово-експертної діяльності в Україні - Simakova-Yefremian, Ella (Теорія та практика судової експертизи і криміналістики, 2023)
The implementation of innovations is a crucial tool for stimulating the development of any process or phenomenon. This is particularly important for developing countries, to which Ukraine belongs, as innovative developments and new knowledge empower a state to enhance the productivity of its economy, thereby providing its competitiveness in global markets. It is precisely this stimulation that fosters econom- ic growth while simultaneously ensuring employment for the population. In turn, the development and implementation of innovations effectively contribute to future scientific research and technical explorations.